2014
DOI: 10.1182/blood-2013-10-533869
|View full text |Cite
|
Sign up to set email alerts
|

B-cell prolymphocytic leukemia: a specific subgroup of mantle cell lymphoma

Abstract: Key Points On the basis of its immunophenotype and gene expression profile, B-PLL may be considered a specific subgroup of MCL. B-PLL is part of a spectrum ranging from CLL-like B-PLL, to leukemic MCL-like B-PLL, to nodal MCL-like B-PLL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 40 publications
2
17
1
Order By: Relevance
“…Manufacturers of automated hematology analyzers appear to have devised complicate strategies to cope with various pathological patterns. The current trend is to use additional morphological parameters of cells, other than the size and complexities of the cell structures detected by the radar beam, for better classification in the multi-dimensional scale [11,12]. However, in this study, we explored the feasibility of improving the classification by use of the newly developed SPC/ITC method even from the conventional 2D scatterplot generated by the Horiba hematology analyzer.…”
Section: Discussionmentioning
confidence: 96%
“…Manufacturers of automated hematology analyzers appear to have devised complicate strategies to cope with various pathological patterns. The current trend is to use additional morphological parameters of cells, other than the size and complexities of the cell structures detected by the radar beam, for better classification in the multi-dimensional scale [11,12]. However, in this study, we explored the feasibility of improving the classification by use of the newly developed SPC/ITC method even from the conventional 2D scatterplot generated by the Horiba hematology analyzer.…”
Section: Discussionmentioning
confidence: 96%
“…1 Some cases with >55% prolymphocytes which had been classified as B-PLL were shown to harbour a translocation t (11;14)(q13;q32) involving the IGH and CCND1 genes, and these were reclassified as MCL in the 2008 WHO classification. 1 Using immunophenotyping and gene expression profiling, van der Velden et al 33 were able to separate B-PLL patients from CLL patients but there was no clear separation from MCL. There were no significant differences between patients with or without t (11;14), suggesting that B-PLL lacking t(11;14) is related closely to MCL.…”
Section: L L a N D I T S R E L A T I O N S H I P T O B -P L Lmentioning
confidence: 99%
“…It was hypothesized that B-PLL is part of a spectrum ranging from close to CLL to fully overlapping with MCL, resulting in CLL-like B-PLL, leukaemic MCL-like B-PLL and nodal MCL-like B-PLL. 33 Using gene expression profiling, Del Giudice et al 34 had shown previously that B-PLL and CLL (including CLL/PLL with >10% and <55% prolymphocytes) are biologically distinct diseases, each showing a specific and homogeneous genomic signature. It is clear from these observations that cases of CLL manifesting >10% prolymphocytes in the PB are examples of progression of the original disease to a more aggressive phase rather than transformation to a new type of lymphoid neoplasm.…”
Section: L L a N D I T S R E L A T I O N S H I P T O B -P L Lmentioning
confidence: 99%
“…Van der Velden et al [20] evaluated seven B cell prolymphocytic leukemia (B-PLL) cases with a t(11;14) (B-PLL+), now referred to as mantle cell lymphoma (MCL) and compared them with six without the translocation (B-PLL−). EuroFlow-based immunophenotyping showed significant overlap between B-PLL+ and B-PLL−, as well as between B-PLL and MCL, whereas CLL clustered separately.…”
Section: New Entities/subtypesmentioning
confidence: 99%